2013
DOI: 10.3988/jcn.2013.9.3.151
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Fluorodeoxyglucose Positron Emission Tomography Findings in Patients with Phenylketonuria before and during Sapropterin Supplementation

Abstract: Background and PurposePET scanning with fluorodeoxyglucose (FDG-PET) is a non-invasive method that measures regional glucose metabolic rate. Phenylalanine (Phe) and its metabolites appear to impair several aspects of brain energy metabolism. 1) To evaluate brain glucose metabolism with FDG-PET imaging in phenylketonuria (PKU) patients before and 4 months after sapropterin therapy; 2) to evaluate neurodevelopmental changes, blood Phe levels and dietary Phe tolerance before and after sapropterin therapy; 3) to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…CMR glc studies in human PKU patients are sparse and difficult to compare with those in animals due to a heterogeneous patient population with differences in age, diet, and clinical intervention. Global energy metabolism is, however, intact in PKU patients, as in the rats, and there are selective changes in relatively few brain structures but affected regions differ among the studies [38, 6769]. …”
Section: Discussionmentioning
confidence: 99%
“…CMR glc studies in human PKU patients are sparse and difficult to compare with those in animals due to a heterogeneous patient population with differences in age, diet, and clinical intervention. Global energy metabolism is, however, intact in PKU patients, as in the rats, and there are selective changes in relatively few brain structures but affected regions differ among the studies [38, 6769]. …”
Section: Discussionmentioning
confidence: 99%
“…The study was limited by a small sample size (5 subjects) and none had responded to sapropterin therapy; defined as 30% decrease in blood Phe level. In addition, gglucose metabolism also appeared depressed in the cerebellum and left parietal cortex while elevated in the frontal and anterior cingulate cortices as well as in left Broca's area and right superior lateral temporal cortex bilaterally [79] .…”
Section: Fabry Diseasementioning
confidence: 92%
“…81 The role of such impaired cerebral energy metabolism on brain functioning in PKU is however largely unknown. Reduced cerebral energy metabolism has been suggested to relate to white matter abnormalities in PKU, 78 while increased cerebral glucose metabolism, which has been observed in particular brain areas in PKU patients, 77,80 has been suggested to reflect some compensatory mechanism. 77 The effect of BH 4 (at 20 mg/kg/day) on brain glucose metabolism as measured by FDG-PET has been investigated in one study in BH 4 -unresponsive PKU patients.…”
Section: Bh 4 and Cerebral Energy Metabolismmentioning
confidence: 99%
“…Reduced cerebral energy metabolism has been suggested to relate to white matter abnormalities in PKU, 78 while increased cerebral glucose metabolism, which has been observed in particular brain areas in PKU patients, 77,80 has been suggested to reflect some compensatory mechanism. 77 The effect of BH 4 (at 20 mg/kg/day) on brain glucose metabolism as measured by FDG-PET has been investigated in one study in BH 4 -unresponsive PKU patients. 77 This study showed that, after 4 months of BH 4 treatment, glucose metabolism in left Broca's and right lateral temporal cortices was increased, which was accompanied by enhanced performance in a phonemic fluency test.…”
Section: Bh 4 and Cerebral Energy Metabolismmentioning
confidence: 99%
See 1 more Smart Citation